# Solve using the Square Root Property 5x^2+10x-30=0 5×2+10x-30=0
Factor 5 out of 5×2+10x-30.
Factor 5 out of 5×2.
5(x2)+10x-30=0
Factor 5 out of 10x.
5(x2)+5(2x)-30=0
Factor 5 out of -30.
5×2+5(2x)+5⋅-6=0
Factor 5 out of 5×2+5(2x).
5(x2+2x)+5⋅-6=0
Factor 5 out of 5(x2+2x)+5⋅-6.
5(x2+2x-6)=0
5(x2+2x-6)=0
Divide each term by 5 and simplify.
Divide each term in 5(x2+2x-6)=0 by 5.
5(x2+2x-6)5=05
Cancel the common factor of 5.
Cancel the common factor.
5(x2+2x-6)5=05
Divide x2+2x-6 by 1.
x2+2x-6=05
x2+2x-6=05
Divide 0 by 5.
x2+2x-6=0
x2+2x-6=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=2, and c=-6 into the quadratic formula and solve for x.
-2±22-4⋅(1⋅-6)2⋅1
Simplify.
Simplify the numerator.
Raise 2 to the power of 2.
x=-2±4-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-2±4-4⋅-62⋅1
Multiply -4 by -6.
x=-2±4+242⋅1
Add 4 and 24.
x=-2±282⋅1
Rewrite 28 as 22⋅7.
Factor 4 out of 28.
x=-2±4(7)2⋅1
Rewrite 4 as 22.
x=-2±22⋅72⋅1
x=-2±22⋅72⋅1
Pull terms out from under the radical.
x=-2±272⋅1
x=-2±272⋅1
Multiply 2 by 1.
x=-2±272
Simplify -2±272.
x=-1±7
x=-1±7
Simplify the expression to solve for the + portion of the ±.
Simplify the numerator.
Raise 2 to the power of 2.
x=-2±4-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-2±4-4⋅-62⋅1
Multiply -4 by -6.
x=-2±4+242⋅1
Add 4 and 24.
x=-2±282⋅1
Rewrite 28 as 22⋅7.
Factor 4 out of 28.
x=-2±4(7)2⋅1
Rewrite 4 as 22.
x=-2±22⋅72⋅1
x=-2±22⋅72⋅1
Pull terms out from under the radical.
x=-2±272⋅1
x=-2±272⋅1
Multiply 2 by 1.
x=-2±272
Simplify -2±272.
x=-1±7
Change the ± to +.
x=-1+7
x=-1+7
Simplify the expression to solve for the – portion of the ±.
Simplify the numerator.
Raise 2 to the power of 2.
x=-2±4-4⋅(1⋅-6)2⋅1
Multiply -6 by 1.
x=-2±4-4⋅-62⋅1
Multiply -4 by -6.
x=-2±4+242⋅1
Add 4 and 24.
x=-2±282⋅1
Rewrite 28 as 22⋅7.
Factor 4 out of 28.
x=-2±4(7)2⋅1
Rewrite 4 as 22.
x=-2±22⋅72⋅1
x=-2±22⋅72⋅1
Pull terms out from under the radical.
x=-2±272⋅1
x=-2±272⋅1
Multiply 2 by 1.
x=-2±272
Simplify -2±272.
x=-1±7
Change the ± to -.
x=-1-7
x=-1-7
The final answer is the combination of both solutions.
x=-1+7,-1-7
The result can be shown in multiple forms.
Exact Form:
x=-1+7,-1-7
Decimal Form:
x=1.64575131…,-3.64575131…
Solve using the Square Root Property 5x^2+10x-30=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top